History of reptile placentology, part III: Giacomini's 1891 histological monograph on lizard placentation. (December 2017) - Blackburn, D.G.; Paulesu, L.; Avanzati, A.M.; Roth, M.
Abstract: By the 1890s, placental arrangements had been documented macroscopically in lizards and fishes, but placental studies on such species lagged far behind research on mammals. In 1891, the biologist Ercole Giacomini (at the University of Siena, Italy) published the first histological analysis of a reptile placenta. Focusing on a placentotrophic lizard ( Chalcides chalcides ) with a morphologically complex placenta, Giacomini documented the histological and cellular bases for placental nutrient transfer and gas exchange. In conjunction with a follow-up study in 1906, he demonstrated that placental structure is correlated with function and can vary dramatically between related species. Giacomini's work was highly influential in showing that placentation in lizards had converged evolutionarily on that of mammals, while establishing reptile placentology as a highly promising area for future research. Highlights: Giacomini's study was the first to analyze microscopic anatomy of a reptile placenta. His monograph revealed the anatomical basis for nutrient transfer and gas exchange. It showed that placental features had converged evolutionarily on those of mammals. Giacomini's structural and functional inferences were corroborated by later work. His classic paper is one of the most influential in the history of placentology.